1988
DOI: 10.1016/0304-3959(88)90288-6
|View full text |Cite
|
Sign up to set email alerts
|

Phantom limb pain in amputees during the first 12 months following limb amputation, after preoperative lumbar epidural blockade

Abstract: The similarities between phantom limb pain and preoperative limb pain have been noted, and this raises the possibility of modulating the pain by a preoperative blockade. The aim of this study was to investigate if it was possible to reduce postoperative phantom limb pain by giving lumbar epidural blockade (LEB) with bupivacaine and morphine for 72 h prior to the operation. 25 patients were interviewed about their limb pain before limb amputation, and about their phantom limb pain 7 days, 6 months and 1 year af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
0
39

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 505 publications
(152 citation statements)
references
References 9 publications
6
107
0
39
Order By: Relevance
“…Probably related to this, postamputation pain seems to be more common in amputation for cancer rather than trauma [19]. A great deal of excitement was engendered when Bach et al reported a significant decrease in the incidence of phantom limb pain attributable to the use of 72 hours dense epidural blockade prior to amputation in a quasirandomized but small trial [30]. This study strongly suggested that "pre-emptive" analgesia worked, at least in the case of limb amputation.…”
Section: Lower Extremity Amputationmentioning
confidence: 96%
“…Probably related to this, postamputation pain seems to be more common in amputation for cancer rather than trauma [19]. A great deal of excitement was engendered when Bach et al reported a significant decrease in the incidence of phantom limb pain attributable to the use of 72 hours dense epidural blockade prior to amputation in a quasirandomized but small trial [30]. This study strongly suggested that "pre-emptive" analgesia worked, at least in the case of limb amputation.…”
Section: Lower Extremity Amputationmentioning
confidence: 96%
“…Das Studiendesign war bei 3 Studien prospektiv, randomisiert [1,7,9], in einer prospektiv offen [6], einmal offen ohne weitere Angaben [11] und in 4 Untersuchungen retrospektiv [2,12,14,16].…”
Section: Ergebnisseunclassified
“…Bei Kontrollgruppen, die eine systemische Analgesie erhielten,zeigte sich im Verlauf ein Trend zu Spontanremissionen (Tabelle 3) [1,7].Dabei wurde eine Reduktion der Phantomschmerzprävalenz nach einem Jahr auf 25-30% der akuten postoperativen Prävalenz angegeben [1,7]. Diese Angabe finden sich jedoch nicht bei allen Untersuchungen [6].…”
Section: Ergebnisseunclassified
See 2 more Smart Citations